(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2012)
Alaverdi ore area formed on the NW edge of the anticlinorium, bearing the same name is limited by NE faults on mafic block of metamorphic basement of the crust and its adjacent territories. The analysis of the results of geological-surveying, prospecting and estimating, gravi-magnetometric and geochemical researches made it possible to allocate and pre-estimate the ore area and the ore knots and ore fields located within its limits.